2015
DOI: 10.3109/08923973.2015.1005229
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of garlic 14-kDa protein on LPS-stimulated-J774A.1 macrophages

Abstract: Our results suggested, for the first time, garlic 14-kDa protein exhibits anti-inflammatory properties in macrophages possibly by suppressing the inflammatory mediators via the inhibition of transcription factor NF-κB signaling pathway. The traditional use of garlic as anti-inflammatory remedy could be ascribed partly to 14-kDa protein content. This protein might be a useful candidate for controlling inflammatory diseases and further investigations in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Zamani Taghizadeh Rabe et al found that 14-kDa protein in allicin affected the expressions of inflammatory cytokines such as NO, TNF-α, and interleukin (IL) 1β by inhibiting LPS-stimulated J774A in the NF-κB signaling pathway. 63 This is also consistent with the anti-inflammatory, antibacterial, and vascular repair functions of the H 2 S donor allicin in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Zamani Taghizadeh Rabe et al found that 14-kDa protein in allicin affected the expressions of inflammatory cytokines such as NO, TNF-α, and interleukin (IL) 1β by inhibiting LPS-stimulated J774A in the NF-κB signaling pathway. 63 This is also consistent with the anti-inflammatory, antibacterial, and vascular repair functions of the H 2 S donor allicin in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Kim et al (2017) claimed that after the treatment of RAW 264.7 cells with black A. sativum bulb-derived components, their cell viabilities did not significantly change [24]. A 14 kD protein derived A. sativum bulb had no impact on J774A.1 macrophage viability at 5-30 µg/mL [25]. According to Lee et al A. sativum bulbderived organosulfur compound of Diallyl Trisulfide (DATS) had no effect on murine RAW 264.7 macrophage cell viability at lower concentrations (10-30 µM) [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the ethyl linoleate in garlic reduced the production of nitric oxide (NO) and prostaglandin E-2 by down-regulating the expression of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX2) in lipopolysaccharide-stimulated RAW 264.7 macrophages [45]. Another study revealed that the garlic 14-kDa protein inhibited the inflammatory mediators including NO, TNF-α, and interleukin (IL) -1β by inhibiting the transcription factor nuclear factor-kappa B (NF-κB) signaling pathway in lipopolysaccharide-stimulated J774A.1 macrophages [46]. In addition, AGE inhibited inflammation in apolipoprotein E-knockout mice.…”
Section: Biological Functions Of Garlicmentioning
confidence: 99%